Incidencia De La Cadena De Valor En El Desarrollo Sustentable Del Cultivo De Café Robusta (Coffea Canephora) Estudio De Caso: Parroquia San Jacinto Del Búa, Provincia De Santo Domingo De Los Tsáchilas - Ecuador - Guadalupe, Carla Sofía Arguello; Ruiz, Juan Eduardo León; Moyota, Paulina Beatriz Díaz; Bernal, Catalina Margarita Verdugo; Mena, Mayra Elizabeth Caceres; Rosero, Ligia Magali García; Granda de Freitas, Josiane; Saavedra Gallo, Christian Gerardo (European Scientific Journal, ESJ, 2017)
The research has as its objective, determine the incidence of the value chain in the sustainable development of the cultivation of Robust Coffee (Coffea canephora) in San Jacinto del Búa parish, Santo Domingo de los Tsáchilas province. From this, arose a line based on coffee farms, also analyzing Robusta coffee value chain and was drafted the proposal for the development of producers under a sustainable approach. The methodology was not experimental but used deductive, inductive and analytical methods. The diagnosis identified the existence of a culture of international quality, with negative factors such as low unfavorable yields from cultivation, inadequate income, living conditions, all this coupled with the lack of environmental awareness in the producers and marketers. At the same time the value chain shows the low percentage of participation by the producer in the seven marketing channels identified. So it proposed 9 economic indicators, 10 social 7 environmental and 13 technical and productive indicators as a basis for future monitoring of this agricultural activity. Also a plan for sustainable development which contains 30 strategies that will improve the economic, social, environmental was developed and will be displayed in the area.